ADAPTASI TRANSKULTURAL KUESIONER PAINDETECT KE DALAM BAHASA INDONESIA - Karolina Margareta,* Tiara Aninditha,* Manfaluthy Hakim,* Herqutanto,** Mohammad Kuniawan* (Neurona Majalah Kedokteran Neuro Sains, 2017)
INTRODUCTION NEUROPATHIC PAIN IS NOT EASILY DETECTED DUE TO LACK OF AN IDEAL SCREENING INSTRUMENT MANAGEMENT OF NEUROPATHIC PAIN AND NOCICEPTIC PAIN ARE DIFFERENT NEVERTHELESS INADEQUATE MANAGEMENT OF NEUROPATHIC PAIN WILL LEADS TO CHRONIC PAIN THAT IMPAIR QUALITY OF LIFE PAINDETECT QUESTIONAIRE HAS A HIGH SENSITIVITY AND SPECIFICITY TO IDENTIFY NEUROPATHIC PAIN AND ALREADY HAS BEEN TRANSLATED TO VARIOUS LANGUAGE BUT NOT TO INDONESIAN LANGUAGE